Teachers' response to standards-based reform: Probing reform assumptions in Washington State. - Loeb, Hilary; Knapp, Michael S.; Elfers, Ana M. (Education Policy Analysis Archives, 2008)
Because teachers' efforts are central to the success of standards-based reform, it behooves the policy community to look carefully at the beliefs about instruction that are rooted in this reform theory. Building on teacher-centric research on standards-based reform and ideas about teaching practice from research on multicultural education, this paper focuses on the assumptions embedded in Washington state's approach. Survey data from a representative sample of teachers suggest that the state's program of high student learning standards, aligned assessments and an accountability system has shaped teachers' instructional practice and their students' learning in ways that the state's reform theory assumes. However, teachers' concerns about student achievement and instructional supports indicate problems with the inherent logic of the state's reform regarding how well it serves a diverse student population.